2002
DOI: 10.4315/0362-028x-65.9.1452
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the 3M Petrifilm Enterobacteriaceae Count Plate Method for the Enumeration of Enterobacteriaceae in Foods

Abstract: Results of the 3M Petrifilm Enterobacteriaceae Count (EB) plate method were compared with those of the standard violet red bile glucose agar (VRBG) method for the detection and enumeration of Enterobacteriaceae. Studies involving 107 bacterial strains demonstrated that the Petrifilm EB plate method is as sensitive as and more selective than the VRBG method. Sixty of the 62 pure Enterobacteriaceae cultures were recovered by both methods. In addition, 38 of the 45 non-Enterobacteriaceae organisms did not grow on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 1 publication
2
7
0
Order By: Relevance
“…A different result was reported by Silbernagel and Linderberg (2003), who in a study on artificial contamination with Proteus vulgaris at different inoculum levels in milk samples evaluated the performance of the Petrifilm EB system and compared the results to those obtained with the plate count method and the Most Probable Number (MPN) technique. In this study, the results showed that there was no statistical difference between the methods at an medium level of inoculation (10 3 CFU mL −1 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A different result was reported by Silbernagel and Linderberg (2003), who in a study on artificial contamination with Proteus vulgaris at different inoculum levels in milk samples evaluated the performance of the Petrifilm EB system and compared the results to those obtained with the plate count method and the Most Probable Number (MPN) technique. In this study, the results showed that there was no statistical difference between the methods at an medium level of inoculation (10 3 CFU mL −1 ).…”
Section: Discussionmentioning
confidence: 89%
“…Silbernagel and Lindberg (2002) also conducted a similar study with 174 samples of naturally contaminated and 120 artificially contaminated dairy and non-dairy products, inoculated with three different inoculum levels (low, medium and high) and 45 pure non- Enterobacteriaceae strains and 65 pure cultures of Enterobacteriaceae , with the aim of evaluating the Petrifilm™ EB system and compare it against the performance of the VRBG Standard Method. The results showed that the Petrifilm™ EB system had an equal or better performance than the VRBG standard method and showed to be sensitive with a recovery rate of 97% of the Enterobacteriaceae present and also selective with only 16% of the non- Enterobacteriaceae being capable to grow on the Petrifilm™ EB plate.…”
Section: Discussionmentioning
confidence: 99%
“…Silbernagel and Lindberg (2002) worked with dairy and nondairy foods using naturally contaminated and artificially inoculated samples and concluded that the 3M Petrifilm EB plate method performed as well as or better than the standard VRBG method.…”
Section: Resultsmentioning
confidence: 97%
“…As a conservative rule, values recorded as ,1.0 CFU/ml were transformed to 0.1 CFU/ml and those recorded as ,10.0 CFU/ml were transformed to 1.0 CFU/ml. Colony counts or MPN estimates were converted to log counts to more nearly match the underlying assumption of a normal distribution (13). Means, standard deviations, t test P values, and appropriate correlation coefficients were determined in R (11) using only the normalized values that were greater than 0.…”
Section: Methodsmentioning
confidence: 99%